FORMULASI EKSTRAK ETANOL DAGING BUAH PEPAYA (Carica papaya LINN) DALAM BASIS LOTION, UJI SIFAT FISIK DAN NILAI SPFNYA - Febrianika Ayu Kusumaningtyas; Iis Wahyuningsih; Nining Sugihartini (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Human skin is intensely exposed to the factors that risk causing irritation and damage. Carica papaya Linn is a fruit which rich in phenolic and flavonoids compounds that has an activity to ward off Ultraviolet Radiation (UVR). This research aims to formulate lotion with 1% (F1), 3% (F2) and 5% (F3) of concentration of papaya fruit extract, then tested the physical properties including pH test, viscosity, flow properties, spreadability, adhesivity and activity test as a sunscreen to determine the SPF value. Results showed that the presence of extracts and increased of its concentrations affected the spreadability, viscosity of the lotion and the value of SPF significantly, but had no significant effect on adhesivity, pH and physical stability. It can be concluded that papaya fruit extract lotion meets the dosage requirements, physically stable and has activity as a sunscreen.